PENGARUH BUDAYA ORGANISASI TERHADAP EFEKTIVITAS SEKOLAH (Studi Kasus Pada SDN 1 Karangsari Waled Cirebon) - eulin, Rini, Dedi karlina, Martiwi, suharyadi (Universitas Bina Sarana Informatika, 2018)
The purpose of this study is to determine the effect of organizational culture on the effectiveness of schools in Elementary School 1 Karangsari waled, Cirebon. This research uses descriptive quantitative method with data collection method using Questionnaire. The result of this research is from correlation coefficient test known that the relation between organizational culture variable and school effectiveness 0,521 means that the relationship between the two variables is strong, if organizational culture increases then school effectiveness increases. While the results of coefficient of determination of the influence between organizational culture with school effectiveness of 34% and the remaining 66% influenced by other factors. And test result of regression equation Y = 13,116 + 5,320X which means constant rate from Unstandardized Coefficients which in this research is -13,116 this figure is constant number which have meaning if there is no additional 1 organizational culture then effectiveness of indirect school will decrease equal to 13,116. Regression coefficient rate of +5,320 which means each addition of 1 school effectiveness then the organizational culture will increase.